Spreading fun: Comic zombies, Joker viruses and COVID-19 jokes. Issue 1 (1st April 2021) - Jürgens, Anna-Sophie; Fiadotava, Anastasiya; Tscharke, David; Viaña, John Noel
This article examines the interplay between humour, science and pandemics in culture. Asking what comic scenarios of infectious diseases look like in different media, the article focuses on comic zombiism in film, clown viruses in comics and COVID-19 jokes on the internet. What can we learn from comic zombies and the Joker ‐ the clown prince of crime in the DC Universe ‐ about infectious diseases? What do viral jokes about pandemics in popular communication (COVID-19 memes in particular) that explicitly refer to these pop cultural phenomena teach us about our understanding of the spread of diseases? And in what way is the spread of humour comparable to the spread of viruses? Exploring these questions, this article investigates the ways humorous interpretations of infectious diseases shape, cultivate and reinforce cultural meanings of diseases and science.